Analysis of Fortnightly and Monthly Tides - Crawford, W. R. (The International Hydrographic Review, 2015)
The fortnightly and monthly tidal constituents can be extracted from tidal records if care is taken in the analysis. One year of observations may be insufficient to resolve these constituents from the meteorologically forced background noise. In this paper, I describe a procedure to reduce the background noise, and to determine the amplitude, phase and uncertainties of these constituents. Analysis is performed on records from four ports in western Canada, at a latitude where air pressure changes and winds cause significant sea level changes.